Successful medical treatment for globe penetration following tooth extraction in a dog. (21st July 2013) - Guerreiro, Cleo E.; Appelboam, Helen; Lowe, Robert C.
Abstract A five‐year‐old entire male Tibetan Terrier was referred for left‐sided periorbital swelling and blepharospasm 4 days following ipsilateral maxillary tooth extraction. Examination of the left eye revealed mild exophthalmos, pain on retropulsion, and absent menace response and pupillary light reflexes. Examination of the posterior segment was not possible owing to the anterior segment pathology. Differential diagnoses considered were iatrogenic globe penetration and peribulbar abscess/cellulitis. Ocular ultrasound was consistent with a penetrating wound to the globe. Treatment with systemic prednisolone and marbofloxacin, and topical atropine sulfate 1%, prednisolone acetate, and brinzolamide was started. Marked clinical improvement allowed visual confirmation of the perforation. Oral prednisolone was tapered over the following 10 weeks. At final re‐examination (10 months), the patient was visual, and fundic examination revealed an additional chorioretinal scar, most likely an exit wound that was obscured by vitreal debris on initial examinations. Neither scar was associated with retinal detachment. To the authors' knowledge, this is the first reported case of successful medical management of iatrogenic globe penetration following exodontic procedures.